2002
DOI: 10.1053/joca.2002.0828
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte apoptosis following intraarticular fracture in humans

Abstract: The percentage of TUNEL positive chondrocytes following intraarticular fracture is much higher than that reported for chronic degenerative conditions such as osteoarthritis and rheumatoid arthritis. These data provide strong evidence that chondrocyte apoptosis is a consequence of intraarticular fracture and suggest that chondrocyte apoptosis may play a particularly significant role in the subsequent development of post-traumatic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 11 publications
6
77
0
Order By: Relevance
“…Many studies have indicated significant correlations between OA grade and chondrocyte apoptosis [Kim et al, 2002].…”
Section: Ginger ( Z Officinalementioning
confidence: 99%
“…Many studies have indicated significant correlations between OA grade and chondrocyte apoptosis [Kim et al, 2002].…”
Section: Ginger ( Z Officinalementioning
confidence: 99%
“…It is well established that wounding of articular cartilage leads to apoptotic and necrotic cell death at the lesion edge [2][3][4][5][6][7] ; thus, cartilage tissue integration is likely impaired by a lack of live or viable cells at the interface region that are capable of producing a functional repair tissue. 8,9 In addition, this is hindered by the inherent limited ability of chondrocytes to migrate through the extracellular matrix toward the acellular interface region.…”
Section: Introductionmentioning
confidence: 99%
“…Chondrocyte apoptosis has also been shown in human biopsy tissue near sites of chondral fracture [15]. Canine cartilage explants subjected to 5 MPa of cyclic compression at 0.3 Hz exhibited the development of both necrosis and apoptosis, increasing progressively with load duration and time.…”
Section: Resultsmentioning
confidence: 91%